2n-1=-10

Simple and best practice solution for 2n-1=-10 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2n-1=-10 equation:


Simplifying
2n + -1 = -10

Reorder the terms:
-1 + 2n = -10

Solving
-1 + 2n = -10

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '1' to each side of the equation.
-1 + 1 + 2n = -10 + 1

Combine like terms: -1 + 1 = 0
0 + 2n = -10 + 1
2n = -10 + 1

Combine like terms: -10 + 1 = -9
2n = -9

Divide each side by '2'.
n = -4.5

Simplifying
n = -4.5

See similar equations:

| 11=4(x-1)-x | | 2600=(2x-6)m+(x+3)m | | 4x+5=16x+8-12x-3 | | 1.8x+2.8=2.5*2.1 | | -108=3(4+8n) | | 2[4x+1]+5=19 | | (8x-12)(5x-25)=0 | | (a)3.43x=5.6 | | 2[4x+1]5=19 | | 7(y-3)=4y-33 | | 25=3+9x | | 2+.142x=9 | | 3b-2=14 | | 2a-7=4(3a+1)-2 | | -6x-x+10=16-7x-5 | | 3x-5(x-5)=-7+4x-16 | | (-3)(-2)+(-2)(4)= | | 12+5x=-2x-11 | | 13=1-7x-5x | | X^2-15x-1000=0 | | (7y+x)=4 | | y=3x^3+27x^2 | | 8(x+4)=7(2x+3) | | 5(x-4)-3(x-2)=12 | | 2a-17=21 | | 0.22(x+9)=0.2x+3.6 | | =(2x)(3x+1) | | -2w+8-2w=-w-7w+3w | | 0=(2x)(3x+1) | | 39.95+.35m=69.70 | | 2x+3x=2x-4 | | -8-(12-16)= |

Equations solver categories